Empyema thoracis complicated by pneumothorax neccessitans manifesting as lobulated, localized subcutaneous emphysematous swellings - Kuan, Yeh Chunn; How, Soon Hin; Yeen, Wing Choy; Ng, Teck Han; Abdul Rani, Mohammed Fauzi (Elsevier Inc., 2011)
We describe a patient with empyema thoracis that had eroded through the apical chest wall to the supraclavicular fossa and lung parenchyma, ultimately leading to a bronchopleural fistula manifesting as lobulated, localized subcutaneous emphysematous swellings over the chest wall and supraclavicular fossa. This is a rarely reported phenomenon and the reason why the lobulated subcutaneous emphysematous swellings remained localized is unknown